Solutions and Challenges to Low Reading Interest among Students at SMP Negeri 3 Satu Atap Tabona - Sahara, La; Sujinah, Sujinah (Universitas Pahlawan Tuanku Tambusai, 2026)
The low reading interest of junior high school students in remote areas is a serious problem exacerbated by limited infrastructure and access to books, especially in one-roof schools such as SMP Negeri 3 Satu Atap Tabona. This study aims to identify the literacy solutions implemented and the internal and external challenges faced. Using a qualitative case study design approach, the population included the entire school community with purposive and snowball sampling until data saturation from 7 key informants (principal, teachers, students, librarian). The instruments consisted of semi-structured interview guides, participant observation, and document analysis, analyzed using the Miles and Huberman model and thematic analysis. The results showed that the 15-minute reading program and library visits were ineffective, while review competitions and assignment integration received the highest positive response (83%). The main challenges include outdated book collections, minimal infrastructure, gadget distractions, low family support, and geographic isolation. The study concluded the need for a holistic, contextual strategy that transforms a quantitative approach into a meaningful reading experience through competitive activities and community partnerships.